Fluorometric Determination of Nucleic Acids Using A Fluorescence-Enhancing Method - Jia, Zhen (Asian Journal of Chemistry, 2010)
It was found that the fluorescence intensity of gadolinium-quercetin system was greatly enhanced by nucleic acids in the presence of sodium dodecyl benzene sulfonate. Based on this, nucleic acids can be sensitively determined by the fluorescence technique. The enhanced fluorescence intensity was proportional to the concentration of nucleic acids among a wide range. The detection limits ranged from 5.0 to 21 ng/mL depending on the kind of nucleic acids. The interaction mechanism between gadolinium-quercetin-sodium dodecyl benzene sulfonate and nucleic acids was electrostatic binding.